Microvascular reconstructions in oral and maxillofacial surgery: results of a survey among oral and maxillofacial surgeons in Germany, Austria, and Switzerland - Pabst, Andreas; Zeller, Alexander; Raguse, Jan; Hoffmann, Jürgen; Goetze, Elisabeth Johanna (Journal of cranio-maxillofacial surgery, 2023)
This study aimed to evaluate the use of microvascular free flaps (MFF) in oral and maxillofacial surgery (OMFS) in Germany, Austria, and Switzerland. A dynamic online questionnaire, using 42-46 questions, was sent to OMF surgeons based in hospitals in Germany, Austria, and Switzerland. The questionnaire was evaluated internally and externally. Aside from general information, data were collected on organizational aspects, approaches, MFF types and frequency, presurgical planning, intraoperative procedures, perioperative medications, flap monitoring, and patient management. Participants mostly performed 30-40 MFF each year (11/53). Most stated that the COVID-19 pandemic did influence MFF frequency (25/53) to varying extents. Radial forearm flap was most frequently used (37/53), followed by ALT (5/53), and fibula flap (5/53). Primary reconstruction was performed by most participants (35/48). Irradiated bony transplants were mostly used for implant placement after 12 months (23/48). Most participants (38/48) used reconstruction plates, followed by miniplates (36/48), PSI reconstruction (31/48), and PSI miniplates (10/48). Regarding the postoperative use of anticoagulants, low-molecular-weight (37/48) and unfractioned heparins (15/48) were widely used, most often for 3-7 days (26/48). Clinical evaluation was mostly preferred for flap monitoring (47/48), usually every 2 h (34/48), for at least 48 h (19/48). Strong heterogeneity in MFF reconstructions in OMFS was found, especially regarding the timepoints of reconstruction, types of osteosynthesis, and postoperative MFF management. These findings provide the chance to further compare the different treatment algorithms regarding relevant MFF aspects, such as postoperative management. This could create evidence-based treatment algorithms that will further improve the clinical outcomes in MFF reconstructions.
Gesehen am 09.06.2023